Test Automation : a manager's guide - Jose, Boby (BCS, The Chartered Institute for IT, 2021)
The practice of test automation is invaluable for modern software testers. Done well, it significantly increases software testing's efficiency, effectiveness and coverage and is essential for continuous testing and continuous delivery.This comprehensive guide for managers covers test automation in-depth for medium- to large-scale implementations, from the benefits of test automation to defining, building and implementing a test automation approach that is fit-for-purpose, to acquiring and executing test execution tools and frameworks. Industry examples are included throughout the book, templates and checklists can be found in the Appendix.